Enhancement of anti-inflammatory activity of polyphenolic flavonoid rutin by encapsulation - Pensak Jantrawut (2018)
The cellular mechanisms underlying the anti-inflammatory activity of rutin which has been found to have in vivo inhibitory effects merit more evaluation. The effects of rutin and encapsulated-rutin on lipopolysaccharide (LPS)- induced IL-6 secretion, NF-κB expression, as well as protein denaturation were investigated. The secretion of IL-6 was not found to have significantly reduced upon incubation with either rutin or encapsulated-rutin at all concentrations. At 100μg/mL, the cells treated with encapsulated-rutin brought about slightly reduced IL-6 secretion but significantly inhibited NF-kB protein expression and protein denaturation in comparison with rutin. Inflammation can be resolved through many mechanisms. The inhibition of IL-6 and NF-kB can serve not only to terminate inflammation but also to inhibit other cytokines or mechanisms. Further investigations are necessary to clarify, verify and establish the antiinflammatory mechanisms of rutin. Additionally, the encapsulation is an interesting technique for enhancing rutin activity.